PROBLEMS IN TEACHING FOREIGN LANGUAGE (World Science, 2020)
This article discusses the problems of teaching a foreign language at a technical university at the present stage. The problem of deepening cognitive activity, strengthening the independence and creativity of students is one of the stimulating tasks in pedagogy. The modern orientation of education towards the formation of a person’s competence in activities and communication presupposes the creation of didactic and psychological conditions in which a student can show a personal position, individuality, express himself as a subject of training. And, namely, the student is involved in the process of educational activity with varying degrees of activity. The article also describes three levels of cognitive activity of students: reproducing, interpreting and creative. The first level, reproducing, is characterized by the desire of students to understand, remember, reproduce the acquired skills, mastering the ways of performing actions on the model. The interpretation level implies a desire to comprehend the meaning of what is being studied, to apply knowledge and mastered methods of activity in new educational conditions. The creative level, on the other hand, provides students with a readiness for a theoretical understanding of knowledge, an understanding of the connections between objects and phenomena, an independent search for solutions to problems. The article analyzes passive and active learning, depending on the level of cognitive activity of students in the educational process. With passive learning, the student acts as an object of educational activity (monologue lectures, reading literature, demonstrations) and does not perform any problematic, search tasks. With active learning, the student becomes the subject of educational activity, enters into a dialogue with the teacher, actively participates in the cognitive process, performs creative, search, problem tasks. Moreover, in this article, based on the objective laws of the process of cognitive activity of a person, information on problem education is given. And, namely, the basis of the theory of problem-based education is: 1. purposefulness (i.e. not one goal is to study the material, but several - educational, educational, developing); 2. The problematic structure of educational material; 3. A combination of creative and reproductive teaching methods; 4. duality of the learning process (the listener is not a passive object of pedagogical activity, but an active subject of the learning process); 5. The corresponding structure of knowledge; 6. systematic motivation for learning (the formation of students' cognitive needs and interest in knowledge). It is also noted that when implementing the principle of problem-based learning, a whole series of psychological and related problems arise, primarily with the creation of a problematic situation corresponding tasks to be solved. This article provides solutions to these problems.